Biological Risk Engineering Handbook: Infection Control and Decontamination - Boss, Martha J (CRC Press, 2009)
This handbook discusses biological risk engineering, an extension of industrial hygiene that involves the assessment, control, and decontamination of indoor biological risks. The book synergizes the knowledge of experts in various fields, from law to toxicology, to provide a compendium of information for applying science to limit biological risk.